Inequality and Greenhouse Gas Emissions : Analysis on Consumption-Based CO2 Emissions, GDP and Income Inequality Across Countries - Värränkivi, Petteri (My University, 2020)
The objective of this thesis is to explore the relationship of greenhouse gas emissions, GDP and inequality across countries. The literature on environment and economic development revolves around the EKC hypothesis, which assumes that at lower levels of income, individuals and countries income increases cause more environmental degradation, but at certain level of income, reaches a tipping point at which increased income begins to improve the state of the environment. Therefore, different levels of income and inequality have an effect on the environmental pressure, based on the marginal propensity of emit at each income levels. An EKC-like inverted U-shape of emissions and income curve is characterized by initially higher marginal emissions that decrease over time and may become negative at high level of income. This is based on the assumption, that at a high enough income, individuals begin to have enough income that they can afford environmentally more sustainable consumption. Based on the relationship between income and emissions, also the relationship between inequality and emissions and will be explored, as redistributing income more equally has an effect on the overall environmental footprint when income is distributed more equally. The effect depends on marginal emissions of individuals as a function of income. In the case of decreasing marginal emissions, redistributing income from high-income individuals to low-income individuals, and increase in emissions is to be expected. Consumption-based CO2 emissions, GDP and Inequality data were studied ion 74 countries over the period of 1990-2015. The country fixed effects estimator found tipping emissions at very high levels of GDP, while inequality was found to have a more adverse effect on emissions at lower GDP levels and higher levels of inequality. Income elasticities of emissions were found to be positive for all but two countries in 2010 and all countries had negative inequality elasticities of emissions based on the fixed effects estimation. These results imply that the two benevolent objectives of abating emissions and decreasing inequality are likely to contradict each other, as decreasing inequality in poorer nations is expected to increase emissions especially in poorer countries and climate change is usually anticipated to have relatively larger impact on poorer communities.

Tämän opinnäytetyön tavoitteena on tutkia kasvihuonekaasupäästöjen, BKT:n ja epätasa-arvon välistä suhdetta kansainvälisellä tasolla. Ympäristötaloustieteen yksi keskeisistä konsepteista on niin sanottu EKC-hypoteesi (Environmenal Kuznet’s Curve), jonka mukaan ympäristöntilan heikkeneminen ja tulotaso muodostavat alaspäin aukeavan parabolin muotoisen käyrän. Tämä tarkoittaa, että matalalla tulotasolla ympäristön tila heikkenee tulojen kasvaessa, kunnes ihmisillä on jollain tulotasolla tarpeeksi varallisuutta kuluttaa niin kestävästi, että ympäristön tila alkaa parantua. EKC-hypoteesin nähdään pitävän paikkaansa monien ympäristön tilaa kuvaavien mittarien kohdalla, mutta kasvihuonekaasupäästöjen kohdalla hypoteesista on myös ristiriitaista näyttöä. Tulojen ja päästöjen välinen vuorovaikutussuhde antaa myös mahdollisuuden mallintaa eriarvoisuuden ja päästöjen välistä suhdetta. Tällöin eri tulojakaumat ja erilaiset tulo-päästökäyrät aiheuttavat erisuuruiset kokonaispäästöt. Mikäli yksilön rajapäästöt ovat EKC-hypoteesin mukaan laskevat, kokonaispäästöt nousevat tasaisemman tulojakauman seurauksena, koska matalamman tulotason henkilöt tuottavat enemmän päästöjä euroa kohti. Tutkimuksen kohteena olivat kulutusperustaiset hiilidioksidipäästöt, bruttokansantuote ja Gini-indeksi 74 maassa ajanjaksolla 1990-2015. Tutkimuksen mukaan päästöjen tulojousto pienenee korkeamman tulotason myötä. Vuodelle 2010 laskettujen päästöjen tulojoustojen arvo oli kuitenkin negatiivinen kahta lukuun ottamatta kaikille maille. Samoin havaittiin, että epätasa-arvon vähentämisellä on suurempi vaikutus päästöihin matalan tulotason ja korkean tulojen epätasa-arvon omaavissa maissa. Tulokset johtavat siihen, että epätasa-arvon vähentäminen ja ilmastonmuutoksen hillintä ovat tavoitteina ristiriidassa keskenään, sillä epätasa-arvon vähentäminen lisää päästöjä, ja toisaalta ilmastonmuutoksella katsotaan olevan isoimmat vaikutukset juuri köyhillä alueilla.
Keywords: Economics, Greenhouse Gas Emissions, Inequality